Analysis of risk factors for intraoperative bleeding in patients with Siewert type II esophagogastric junction adenocarcinoma treated by two minimally invasive surgeries and its influence on prognosis: a retrospective study - Lan, Yang; Shen, Jian; Liu, Ruqian; Jiang, Kai; Qiu, Mingyuan; Wang, Shuai (Frontiers in Oncology, 2024)
BackgroundThe present study aimed to analyze the independent risk factors for intraoperative bleeding in Siewert II adenocarcinoma of the esophagogastric junction (AEG) using two minimally invasive surgical approaches, namely, the laparoscopy-assisted abdominal trans-hiatal (LTH) method and transthoracic-laparoscopic esophagectomy (TLE).MethodsThe clinical data of 100 patients with SiewertII AEG admitted to our hospital from October 2017 to October 2020 were retrospectively analyzed. According to the type of surgery, the patients were divided into LTH approach group and TLE approach group. The differences between the clinical characteristics of the patients in different groups and the differences in the intraoperative bleeding and prognosis between different surgical procedures were analyzed and compared using the t-test and chi-squared test. Multiple linear regression was used to identify the independent risk factors affecting the amount of intraoperative bleeding in patients.ResultsThe results of this study showed that patients in the LTH group had significantly less intraoperative bleeding and operative time and significantly better postoperative recovery than the TLE group. The results of multivariate linear regression showed that the combined trans-thoracic-abdominal approach (P=0.000), advanced age (P=0.014), larger BMI (P=0.000), and larger tumor diameter (P=0.001) were the independent risk factors influencing the increase in intraoperative bleeding.ConclusionIn addition to the conventional factors that affect intraoperative bleeding, such as the patient’s general condition, operation time, and tumor size, LTH surgery is another way to avoid intraoperative bleeding for Siewert type II AEG patients and can significantly improve postoperative recovery.